The Degree of Employment of Teachers of The First Cycle of Basic Education Of Mental Habits in The Teaching of English Language (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The purpose of the research is to identify the degree of employment of teachers of the first cycle of basic education of mental habits in teaching English language, as well as knowledge of the differences in the employment of these habits according to the variables of the academic qualification and the number of years of teaching experience. The sample consisted of (303) teachers and teachers The first cycle of basic education was chosen randomly by the cluster of schools in the first cycle of basic education in Damascus Governorate. They were asked to identify the teachers' use of mental habits in the teaching of the English language by the researcher after verifying its validity and stability. The results indicate that there is a low degree of teachers in the use of mental habits when teaching the English language on the total score of the scale and in all mental habits except the habits of listening comprehension and sympathy, and control of arrogance, thinking about thinking, and finding humor that was a medium. The results showed that there were statistically significant differences between the average teachers on the scale of the use of mental habits in teaching English language according to the variable of scientific qualification for teachers with diploma and postgraduate qualifications. And the existence of statistically significant differences between the average teachers on the scale of the use of mental habits in the teaching of the English language according to the variable years of experience for teachers with (5) years of teaching experience and more except areas (thinking and communicating clearly and accuracy / mutual thinking / risk responsibility) The absence of differences between the members of the research sample according to the variable number of years of experience in these fields.